Electron beam assisted chemical vapor deposition of SiO2 - Collins, G. J., author; Boyer, P. K., author; Emery, K., author; Rocca, Jorge J., author; Thompson, L. R., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1983)
We have demonstrated electron beam assisted chemical vapor deposition of silicon dioxide films on silicon substrates via electron impact dissociation of SiH4, and N2O gas. Dissociation of reactant gases occurs primarily in the confined planar region of the electron beam created plasma. Electron beam deposited SiO2 films have been categorized in terms of their electrical, physical, and chemical properties.